Effectiveness Of Structured Teaching Programme on Impact of Early Marriages and Early Pregnancy Among Middle Adolescent Girls (14-17) Age Group in Selected Rural Community Areas at Peruru - Akumarthi Srilakshmi; Andugula, Swapna Kumari (International Journal of Progressive Research in Science and Engineering, 2024)
A quasi experimental study was conducted A study to assess the effectiveness of structured teaching programme on impact of early marriages and early pregnancy among middle adolescent girls 14-17 age group in selected rural community areas at peruru”.